Importance of new winter pea genotyp in production of the milk on family farms - Gordana Županac; Kristina Gršić; Ana Pisačić; Mihaela Blažinkov; Darko Uher (Mljekarstvo)
Forage pea (Pisum sativum L.) is becoming more represented gorage leguminoza on the fields Republic of Croatia. Three year field trials (2003-2005) were carried out to determine the effect of seed winter pea inoculation and nitrogen top-dressing on productivity of new winter pea genotype G3 in production of milk on family farms. Just before sowing the inoculation of pea seed was performed by the variety of Rhizobium leguminosarum bv. viciae 1001 which is part of the microbiological collection of the Department of Microbiology at the Faculty of Agriculture University of Zagreb. The results of the research showed that the highest total nodule number on pea root (39.7 nodule/plant) as well as nodule dry matter weight (0.203 g/plant) was determined on the inoculated variant. Average highest yield of winter pea dry matter was, once more, determined on the inoculated variant (4.33 t ha-1). Total dry matter yield of winter pea and wheat mixture were ranging from 8.92 t ha-1 (control) up to 10.64 t ha-1 (nitrogen top-dressing). Average highest yield of winter pea crude protein was, once more, determined on the inoculated variant (266 kg ha-1) in 2003, (672 kg ha-1) in 2004 and (853 kg ha-1) in 2005. The conclusion of this research is that the highest dry matter yield (4.33 t ha-1) and crude protein yield was obtained with the inoculation of new genotype winter pea G3.